Stress and metabolic syndrome among adults in Terengganu - Miow, Y.X.; Wee, B.S.; Karimah Fakhriah, I.; Aryati, A. (2018)
Environmental influences such as stress was believed to impact the metabolic disorder, which may progress to cardiovascular disease and type II diabetes. High levels of stress are now emerged as significant health factors among adult nowadays. However, studies on relationship between stress and metabolic syndrome are still scarce. Thus, this study aimed to investigate the association between stress and metabolic syndrome among adult in Terengganu. Subjects comprised 188 adults aged 20 to 59 years old. Anthropometric measurements included weight, height and waist circumferences (WC). Blood pressure (BP) was taken, fasting blood glucose (FBG), triglycerides (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C) and total cholesterol (TC) were determined in overnight fasting blood sample. Harmonized definition on metabolic syndrome was used to identify metabolic risk while stress level was assessed using Depression, Anxiety and Stress Scale-21. A total of 41.0% of male and 59.0% of female were overweight/obese. Prevalence of stress and metabolic syndrome was 17.6% and 39.4%, respectively. There were significant difference of stress score between the ethnicities with Malay showed the highest stress score, followed by Indian and Chinese (p<0.001). There was no significant association between gender, age, ethnicity, body weight status and metabolic syndrome with stress. However, there was significant association between body weight status and metabolic syndrome. Binary logistic regression showed that the odds of developing metabolic syndrome were 9.1 (95% CI: 2.0, 41.1) and 16.8 (95% CI: 3.8, 74.8) times higher in overweight and obese subjects, respectively. The findings of this study showed no significant association between stress and metabolic syndrome. Prospective cohort studies involving larger sample size in determining relationship between stress and metabolic syndrome are needed in future. Appropriate intervention programs should be planned to increase awareness and to promote healthy lifestyles in order to prevent obesity among adult and thus lower metabolic syndrome risk.